THE PERCEPTIONS OF THE TEACHERS ON THE APPLICATION OF PARALLEL PRINCIPLE IN PRIMARY SCHOOLS - Akbaba, Ahmet (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
The aim of this study is presenting the perceptions of teachers on the effects of implementation of the parallel principle on productivity of 1st, 2nd, 3rd and 4th grade primary school students. General screeningmethod was usedin the study. The population of the study consists of 1234 teachers working in 79 primary school of Van in the academic year period of 2013-2014 and the study group consists of 200 classroom teachers from 20 schools, which were selected randomly. The research datawere collectedby questionnairedeveloped by the researcher and the solutions were made with the SPSS program. As a result of the study, it is presented that linking courses increases the knowledge of the students, makes the information transfers and learning the courses easier by solidifying them and facilitates the permanence. Furthermore, the teachers should prepare the syllabuses by considering the common subjects between the courses.